Porous polysilazane-derived ceramic structures generated through photopolymerization-assisted solidification templating. Issue 4 (April 2019) - Obmann, Richard; Schörpf, Sebastian; Gorsche, Christian; Liska, Robert; Fey, Tobias; Konegger, Thomas
Abstract: A novel approach to the preparation of porous polysilazane-derived ceramics is presented, combining non-aqueous solidification templating (freeze casting) of a liquid preceramic polymer with a photo-induced thiol-ene "click" reaction at temperatures below −10 °C. Upon directional solidification of the reaction mixture consisting of the preceramic polymer, a quaternary thiol, a photoinitiator, and camphene as pore-structuring agent, low-temperature photopolymerization of the preceramic polymer was achieved by irradiation with visible light, its feasibility demonstrated by photorheology. Effects of the polymer/structuring agent ratio and the solidification rate on porosity and pore morphology were evaluated using porosimetry and tomography techniques. The structural features were set in relation to mechanical properties, showing compressive strengths up to 74 MPa at porosities between 58% and 76%. This new processing technique facilitates the generation of polysilazane-derived ceramics with highly tailorable pore structures, with prospective uses in processes ranging from membrane-based separation to catalysis.